Monitoring positive mental health and its determinants in Canada: the development of the Positive Mental Health Surveillance Indicator Framework - Orpana, H. (Health Promot Chronic Dis Prev Can, 2016)
INTRODUCTION: The Mental Health Strategy for Canada identified a need to enhance the collection of data on mental health in Canada. While surveillance systems on mental illness have been established, a data gap for monitoring positive mental health and its determinants was identified. The goal of this project was to develop a Positive Mental Health Surveillance Indicator Framework, to provide a picture of the state of positive mental health and its determinants in Canada. Data from this surveillance framework will be used to inform programs and policies to improve the mental health of Canadians. METHODS: A literature review and environmental scan were conducted to provide the theoretical base for the framework, and to identify potential positive mental health outcomes and risk and protective factors. The Public Health Agency of Canada’s definition of positive mental health was adopted as the conceptual basis for the outcomes of this framework. After identifying a comprehensive list of risk and protective factors, mental health experts, other governmental partners and non-governmental stakeholders were consulted to prioritize these indicators. Subsequently, these groups were consulted to identify the most promising measurement approaches for each indicator. RESULTS: A conceptual framework for surveillance of positive mental health and its determinants has been developed to contain 5 outcome indicators and 25 determinant indicators organized within 4 domains at the individual, family, community and societal level. This indicator framework addresses a data gap identified in Canada’s strategy for mental health and will be used to inform programs and policies to improve the mental health status of Canadians throughout the life course.